Structural analysis of protein–DNA and protein–RNA interactions by FTIR, UV-visible and CD spectroscopic methods. Issue 2 (2009) - Tajmir-Riahi Tajmir-Riahi, H. A. H. A.; N'soukpoé-Kossi N'soukpoé-Kossi, C. N. C. N.; Joly Joly, D. D.
Abstract : In this chapter the fundamental question of how does protein–DNA or protein–RNA interaction affect the structures and dynamics of DNA, RNA and protein is addressed. Models for calf-thymus DNA and transfer RNA interactions with human serum albumin (HSA), ribonuclease A (RNase A) and deoxyribonuclease I (DNase I) are presented here, using Fourier Transform Infrared (FTIR) spectroscopy in conjunction with UV-visible and CD spectroscopic methods. In the models considered, the binding sites, stability and structural aspects of protein–DNA and protein–RNA are discussed and the effects of protein interaction on the secondary structures of DNA, RNA and protein were determined.